Carotid intima‐media thickness – a potential predictor for rupture risk of intracranial aneurysms. Issue 7 (22nd October 2013) - Lundervik, Marianne; Fromm, Annette; Haaland, Øystein Ariansen; Waje‐Andreassen, Ulrike; Svendsen, Frode; Thomassen, Lars; Helland, Christian A.
<x xml:space="preserve">Abstract</x> Background Individual assessment of rupture risk of cerebral aneurysms is challenging, and increased knowledge of predictors for aneurysm rupture is needed. Smoking and hypertension are shared risk factors for atherosclerotic disease and cerebral aneurysms, and patients with atherosclerosis have an increased prevalence of intracranial aneurysms. Carotid ultrasound with evaluation of intima‐media thickness (IMT) is a non‐invasive, safe, rapid, well‐validated and reproducible technique for quantification of subclinical atherosclerosis and assessment of cardio‐ and cerebrovascular risk. Increased IMT is associated with elevated risk for ischemic stroke and myocardial infarction, but sparse data exist on carotid ultrasound findings in patients with intracranial aneurysms. Aims The purpose of this study was to investigate carotid IMT in patients with unruptured intracranial aneurysms (UIA) and aneurysmal subarachnoid hemorrhage (aSAH), and to assess if IMT might be associated with aneurysm rupture risk. Methods Patients treated for saccular aneurysms (UIA and aSAH) from February 2011 to August 2012 were included. Standardized high resolution B‐mode ultrasound assessment of carotid arteries was done after aneurysm treatment, and traditional vascular risk factors were recorded. Healthy partners of young patients with ischemic stroke were used as controls. Results 69 patients treated for UIA (n = 28) and aSAH (n = 41) were compared with 80 controls. Mean IMT was higher in patients with aSAH (0·79 mm) than patients with UIA (0·65 mm) and controls (0·63 mm). Multiple multinomial regression analysis comparing aSAH, UIA and control groups demonstrated that IMT was the only variable predicative of aSAH compared to UIA. According to the multiple regression model, the probability of having aSAH compared to non‐rupture increased by 62% for each 0·10 mm increment of mean IMT (RRR = 1·62, P = 0·017). Taking into account only patients harboring intracranial aneurysms, simple binary logistic regression was then applied to the UIA and aSAH groups. According to this model the risk of belonging to the aSAH group increased with higher mean IMT values (OR = 1·40 per 0·10 mm increase of mean IMT, P = 0·024). Conclusion There is an association between IMT and intracranial aneurysm rupture status at the time of aneurysm treatment. Carotid IMT can be a potential predictor of aneurysm rupture. IMT may thus be a possible adjunct in the risk assessment of aneurysm rupture, and a helpful tool in patient risk stratification and counseling.